PEMBENTUK INTENTION TO USE DOMPET DIGITAL MELALUI CONSUMER ATTITUDE - Reyner Jonathan; Yasintha Soelasih (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2022)
This study aims to look at the effect of perceived usefulness, perceived convenience, and security on an intention to use through the consumer attitude towards digital wallet users. This is due to the many developments in payment instruments using digital wallets. The research object is digital wallet users. The data taken were 160 respondents. Retrieval of data using purposive sampling. Purposive sampling is used because the respondents taken have already used digital wallets in their payments. The indicators and variables studied were tested for validity and reliability. The validity test used confirmatory factor analysis by looking at the factor loading value. For reliability, composite reliability (CR) and average extracted variance (AVE) are used. To test the hypothesis, structural equation modeling (SEM) is used. The hypothesis testing results indicate that the variable perceived usefulness and security do not directly influence intention to use. The perceived convenience variable does not have a direct or indirect effect on the intention to use. Meanwhile, perceived usefulness and security variables indirectly affect the intention to use through consumer attitude.